The Role of Effective Communication in Reducing Medication Errors in Pharmacy Practice - Zakiah, Fitri; Nuari, Ris Ayu; Hermawan, Asep (Newinera Publisher, 2024)
Medication errors or errors in administering medications are serious health problems that occur in various health care facilities such as hospitals, clinics, and pharmacies. These errors can occur at the stage of writing prescriptions by doctors, providing and preparing drugs by pharmacists, to administering drugs to patients by nurses or patients themselves. Medication errors can lead to a variety of negative consequences, ranging from mild side effects to life-threatening events. This study aims to examine the role of effective communication in reducing medication errors in pharmacy practice. The research method used is a qualitative approach with an exploratory case study at the Salsabilah pharmacy in Leuwikujang Village, Leuwimunding District, Majalengka Regency and the Salsabilah 2 pharmacy in Trajaya Village, Palasah District, Majalengka Regency. The research sample consisted of health workers (pharmacists and doctors) at the Salsabilah pharmacy in Leuwikujang Village, Leuwimunding District, Majalengka Regency and the Salsabilah 2 pharmacy in Trajaya Village, Palasah District, Majalengka Regency, as well as patients who received services at the pharmacy. The results of the study show that effective communication between health workers and patients can improve patient safety by reducing the risk of medication errors. Good communication helps patients understand the treatment they are receiving, so they can follow instructions correctly and report any other side effects or problems immediately.